Model physical planning bill: Draft OECS model Act (amended by Florabelle Grenade-Nurse). - UNDP/UNCHS (UNDP/UNCHS, 2011)
An Act for the orderly and progressive development of land and to preserve and improve the amenities thereof, for granting permission to develop land and other powers of control over the use of land, the design, construction and occupation of buildings.
Keywords: Development planning Laws, Land development - Legislation / Physical planning - Environmental management, Sustainable development